American flygirl - Ankeny, Susan Tate (Citadel Press, Kensington Publishing Corp., 2024)
In 1932, Hazel Ying Lee, a nineteen-year-old American daughter of Chinese immigrants, sat in on a friend's flight lesson. It changed her life. In less than a year, a girl with a wicked sense of humor, a newfound love of flying, and a tough can-do attitude earned her pilot's license and headed for China to help against invading Japanese forces. In time, Hazel would become the first Asian American to fly with the Women Airforce Service Pilots. As thrilling as it may have been, it wasn't easy. In America, Hazel felt the oppression and discrimination of the Chinese Exclusion Act. In China's field of male-dominated aviation she was dismissed for being a woman, and for being an American. But in service to her country, Hazel refused to be limited by gender, race, and impossible dreams. Frustrated but undeterred she forged ahead, married Clifford Louie, a devoted and unconventional husband who cheered his wife on, and gave her all for the cause achieving more in her short remarkable life than even she imagined possible. American Flygirl is the untold account of a spirited fighter and an indomitable hidden figure in American history. She broke every common belief about women. She challenged every social restriction to endure and to succeed. And against seemingly insurmountable obstacles, Hazel Ying Lee reached for the skies and made her mark as a universal and unsung hero whose time has come.